Thermosetting Coupling Analysis and Parameter Optimization of the Plastic Lining Pump Structure - Lingfeng Tang; Mingwei Liu; Feihong Ma (Advances in Materials Science and Engineering)
In order to obtain the optimum structure of the lining pump under the condition of fluid thermosetting coupling, according to the given design parameters, the structural parameters of the pump were calculated, the three-dimensional geometric model was established, and the flow field analysis was carried out by CFD; the inlet angle βb1, outlet angle βb2, wrap angle φ, inlet diameter D1, and outlet diameter D2 of the impeller were selected as the five factors to design orthogonal experiment, and the results were analyzed by range analysis; then, the efficiency and cavitation allowance were obtained as combined parameters under the evaluation index. The displacement deformation and stress distribution under the condition of the coupling field were obtained by the fluid-solid coupling analysis, and the orthogonal experimental table of the impeller structure of the lining plastic pump was established, and then the orthogonal experimental results are analyzed to obtain the influence of each structural parameter under the condition of each evaluation index and the optimum combination parameters. The influence situation and the best combination parameters under the condition of evaluation index, taking the minimum displacement deformation and minimum stress of impeller as the reference index, and the optimum combination parameters under the condition of minimum displacement and stress were as follows: the inlet diameter D1 was 76 mm, the outlet diameter D2 was 252 mm, the inlet angle was 26°, the outlet angle was 24°, and the wrap angle was 115°. Finally, the 3D printing technology was used to print out the physical model to the hydraulic performance experiment verification.